Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-04-13T16:04:54+02:00
X + 19 - 12x = 1 + 2x(4 + 2)
x + 19 - 12 x = 1 + 8x + 4x
x - 12x - 8x - 4x = - 19 + 1
-23x = -18 /:(-23
x = 0,782608 ~ 0,78
x = 0,78

⅓x + ½x + 7 = x
⅓x + ½x - x = -7 /x6
2x + 3x - 6x = -42
5x - 6x = -42
-x = -42 /:(-1)
x = 42

2x x 4 = 22
2x = 22 /:4
2x = 5,5 /:2
x = 2,75

x + 6 = 17
x = 17 x 6
x = 11

2x + 14 - 12 + x + x = 3x - 11 - 1 - x
2x + x + x - 3x + x = -14 + 12 - 11 - 1
2x = - 14 /: 2
x = (-7)

Proszę o naj ;p